Analisis Beban Kerja, Dukungan Sosial Dan Hubungan Interpersonal Dengan Stres Kerja Pada Perempuan Usia Remaja Bagian Jahit Di Pt X - icha chairunnisa; Nur Asniati Djaali; Lilis Heri Mis Cicih; Muhamad Fajar Maulidi Tanjung (Jurnal Kesehatan Marendeng, 2026)
Work stress is a public health issue that can negatively impact worker productivity and well-being. Adolescent female workers are more susceptible to work stress, given that they are in the psychosocial development phase but already have to deal with the demands of production loads and work environment pressures. This study aims to examine the relationship between workload, social support, and interpersonal relationships with work stress levels among adolescent female workers in the sewing department of PT X. The study was conducted using a quantitative approach using a cross-sectional design. A total of 144 respondents were randomly selected, based on the criteria of 18–24 years of age and working in the sewing department. Data collection used a structured questionnaire and analyzed using the chi-square test and multiple logistic regression. The results of the analysis showed that workload had no significant relationship with work stress (p = 0.008; OR = 3.182). Social support showed an insignificant relationship with work stress (p = 0.888; OR = 0.933), indicating that the formed social support is not optimal. In interpersonal relationships, this study showed a significant correlation with work stress (p = 0.001; OR = 4.388), indicating that good communication and cooperation quality contribute to reducing stress levels. From the results of multiple regression, the only significant variable was poor interpersonal relationships, which had a 4.4 times greater risk of experiencing stress compared to social support and workload. The main conclusion of the study stated that workload and interpersonal relationships significantly influenced the level of work stress in female teenage workers in the sewing section, while social support did not have a consistent effect on work stress or was not significant. The need for proportional workload management, increasing promotion programs and control in the workplace, and strengthening interpersonal relationships as preventive strategies to reduce stress and improve worker welfare.